Pendekatan dan Strategi Efektif dalam Pengelolaan Konflik: Definisi, Pendekatan, Strategi - Shofiyah, Adilatus; Auldina, Betha; Haerani, Alfara; Mu’Allimin (STIT Fatahillah, 2024)
Conflict management is an important skill in organizations and groups to maintain harmony and productivity. Conflict, defined as differences of opinion or clashes of interests between individuals or groups, can have negative impacts if not managed well, but can also be a source of innovation and development. This research aims to identify effective definitions, approaches and strategies in conflict management in order to provide practical guidance for organizations in handling conflict. The research method used is literature study with all information used coming from relevant articles and books. The research results show that an effective approach to conflict management includes integrating, obliging, dominating, avoiding and compromising approaches. These strategies, when implemented appropriately, can reduce tensions, strengthen communication, and build trust between the parties involved. The conclusion of this research emphasizes the importance of selecting approaches and strategies that are adapted to the characteristics of conflict to produce constructive solutions, as well as the importance of developing conflict management skills for organizational members in order to achieve common goals